Evolution of Neuropeptide Precursors in Polyneoptera (Insecta) - Bläser, Marcel; Predel, Reinhard (Frontiers in Endocrinology, 2020)
Neuropeptides are among the structurally most diverse signaling molecules and participate in intercellular information transfer from neurotransmission to intrinsic or extrinsic neuromodulation. Many of the peptidergic systems have a very ancient origin that can be traced back to the early evolution of the Metazoa. In recent years, new insights into the evolution of these peptidergic systems resulted from the increasing availability of genome and transcriptome data which facilitated the investigation of the complete neuropeptide precursor sequences. Here we used a comprehensive transcriptome dataset of about 200 species from the 1KITE initiative to study the evolution of single-copy neuropeptide precursors in Polyneoptera. This group comprises well known orders such as cockroaches, termites, locusts and stick insects. Due to their phylogenetic position within the insects and the large number of old lineages, these insects are ideal candidates for studying the evolution of insect neuropeptides and their precursors. Our analyses include the orthologs of 21 single-copy neuropeptide precursors, namely ACP, AST-C, AST-CC, CCAP, CCHamide-1 and 2, CNMamide, corazonin, CRF-DH, CT-DH, elevenin, HanSolin, NPF-1 and 2, MS, proctolin, RFLamide, SIFamide, sNPF, and trissin. Based on the sequences obtained, the degree of sequence conservation between and within the different polyneopteran lineages is discussed. Furthermore, the data are used to postulate the individual neuropeptide sequences that were present at the time of the insect emergence more than 400 million years ago. The data confirm that the extent of sequence conservation across Polyneoptera is remarkably different between the different neuropeptides. Furthermore, the average evolutionary distance for the single-copy neuropeptides differs significantly between the polyneopteran orders. Nonetheless, the single-copy neuropeptide precursors of the Polyneoptera show a relatively high degree of sequence conservation. Basic features of these precursors in this very heterogeneous insect group are explained here in detail for the first time.